The Influence of Altruistic and Sustainable Orientation on Student Business Innovation for Entrepreneurship: A Case Study of Universal University Students - Eryc; Adrian Leonardus Joviyanto Saragi; Alvin Siswanto; Decholas Valentino Wang; Windi (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of altruistic orientation and sustainable orientation on business innovation of students at Universal University in Batam. The background of the study is based on the increasing attention to sustainable entrepreneurship among students, which emphasizes social values, empathy, and environmental concerns as the basis for business decision-making. The method used is an exploratory quantitative approach through a survey of 71 students who have active businesses. The analysis was conducted with Partial Least Squares – Structural Equation Modeling (SEM-PLS) using SmartPLS 4. The results of the validity and reliability tests showed that all constructs met the statistical criteria (outer loading > 0.70; AVE > 0.50; CR > 0.70), with an R² value of 0.77. The results showed that sustainable orientation had a positive and significant effect on student business innovation. However, altruistic orientation did not have a direct effect on business innovation. Altruistic orientation only had an indirect effect through sustainable orientation , thus forming a partial mediation relationship in this research model. These findings indicate that altruistic values ​​only have an impact on innovation if they are realized through a sustainable orientation in entrepreneurial practice. Theoretically, this research expands the application of value theory and the concept of sustainable entrepreneurship by emphasizing the role of sustainability orientation as a bridge between prosocial values ​​and innovation. Practically, the results of this study can serve as a basis for universities to develop green entrepreneurship programs, sustainable business incubation programs, and social and environmental value-based training for student entrepreneurs.